Body talk, weight status, and pathological eating behavior in romantic relationships. (1st October 2017) - Hart, Ellen; Chow, Chong Man; Tan, Cin Cin
Abstract: This study examined whether engagement in body talk would interact with weight status (body mass index; BMI) to predict pathological eating behaviors among romantically involved adults. Adults ( N  = 137, females = 86.86%, average age = 23.50) involved in a romantic relationship were recruited to complete an online survey about their body image, dietary behaviors, and engagement in body talk. Results indicated that engagement in negative body talk was directly related to higher pathological eating (i.e., drive for thinness, dieting, and bulimia symptoms). Positive body talk, on the other hand, had a significant interaction effect with BMI to predict pathological eating. For individuals with a high BMI, high engagement in positive body talk was associated with increased drive for thinness, dieting, and bulimia symptoms. However, for those with a low BMI, high engagement in positive body talk was protective against pathological eating. These findings suggest that while negative body talk is harmful in general, positive body talk is uniquely problematic for individuals of a higher weight status.